Pendampingan Pembelajaran Al - Qur’an Melalui Media Ayo Belajar Tajwid - Fadhli, Khotim; Taqiyudin, Akhmad; Nashoih, Afif Kholisun; A’izzah, Shilna; Hisyam, M.; Amru, Alfian; Septiawan, Fanni; Uyunin, Alfina; Putri, Nadia (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The Al-Qur'an learning assistance program and increasing understanding of recitation in Ketapangkuning Village aims to improve the skills of reading the Al-Qur'an correctly according to recitation rules for children and TPQ teachers. Based on observations, a number of problems were found, including low understanding of Tajweed among students, lack of motivation to study religion, and limited understanding of Tajweed among some teachers. This program uses the Participatory Action Research (PAR) method, involving teachers, students and guardians of students to work together to find solutions. Various approaches, such as training for teachers, interactive learning for santri, and outreach to santri guardians, are implemented to support sustainable learning. Program evaluation shows an increase in students' understanding of Tajwid through pre-test and post-test results, with the majority of students reaching the